PERAN OTORITAS JASA KEUANGAN DALAM PERLINDUNGAN HUKUM BAGI PENGGUNA PINJAMAN ONLINE ILEGAL (Studi Kasus Pinjol Ilegal di Yogyakarta) - Abdurrazaq Triansyah; Putri Nur Siti Julianti; Nadyva Fakhriyah; Andi M Afif (Cross-border, 2022)
The Financial Services Authority (hereinafter abbreviated as OJK) is an independent institution and is free from intervention of other parties, which have the functions, duties, and authorities of regulation, supervision, examinations, and investigations contained in Law Number 21 of 2011 concerning the Service Authority Finance. This research was conducted with the aim of knowing what regulations were issued by the Financial Services Authority institution to protect consumers who use online loan services, especially in Yogyakarta area and what are the sanctions issued by the Financial Services Authority if the parties financial service actors violate the provisions of the Financial Services Authority regulations. If a financial service actor violates the provisions in OJK regulations, he will be subject to administrative sanctions in the form of written regulations, fines or paying a certain amount of money, restrictions business activities, freezing of business activities, and revocation of business licenses. OJK incorporated the Investment Alert Task Force still finds and blocks illegal online loan services. These illegal online loans, apart from being uncontrollable, also cause a lot of problems for users, some cases have resulted in borrowers ending their lives because they could not pay off their outstanding debts billed by debt collectors.